MiR-1273 g-3p Promotes Malignant Progression and has Prognostic Implications in Prostate Cancer - Chang, Yaxue; Deng, Qian; Guan, Zhenfeng; Cheng, Yongyi; Sun, Yi (Molecular biotechnology, 2022)
Prostate cancer (PCa) is the most popular cancer of mankind. Our study aimed to provide the expression and the predictive significance of miR-1273 g-3p in PCa. Moreover, the effects on cell biological activities were also investigated. The relative expression of miR-1273 g-3p in PCa tissues and cell lines was validated by quantitative real-time PCR. Kaplan–Meier curve and Cox regression analyses were performed to indicate the prognostic value. The implications of miR-1273 g-3p on cell proliferation, migration, and invasion were validated using the CCK-8 and Transwell assay. Our results provided that the expression of miR-1273 g-3p was increased in PCa tissues and cell lines. The levels of miR-1273 g-3p were associated with Gleason score, TNM stage, clinical stage, and lymph node metastasis. Overexpression of miR-1273 g-3p indicated a promising overall survival rate. Cox regression results indicated miR-1273 g-3p might be an independent marker for PCa patients. Silenced miR-1273 g-3p inhibited PCa cell proliferation, migration, and invasion. In total, miR-1273 g-3p was increased in PCa and identified as a therapeutic target and a prognostic factor for PCa patients. Overexpression of miR-1273 g-3p might be an oncogene via accelerating cell proliferation, migration, and invasion.